Enhanced Recombinant Protein Production Under Special Environmental Stress - Chen, Xinyi; Li, Chun; Liu, Hu (Frontiers in Microbiology, 2021)
Regardless of bacteria or eukaryotic microorganism hosts, improving their ability to express heterologous proteins is always a goal worthy of elaborate study. In additional to traditional methods including intracellular synthesis process regulation and extracellular environment optimization, some special or extreme conditions can also be employed to create an enhancing effect on heterologous proteins production. In this review, we summarize some extreme environmental factors used for the improvement of heterologous protein expression, including low temperature, hypoxia, microgravity and high osmolality. The applications of these strategies are elaborated with examples of well-documented studies. Then, we also demonstrated the confirmed or hypothetical mechanisms of environment stress affecting the host behaviors. In addition, multi-omics techniques driving the stress-responsive research for construction of efficient microbial cell factories are also prospected at the end.